Company productivity increases with more knowledge-based capital - Heike Belitz; Marie Le Mouel; Alexander Schiersch (DIW Weekly Report, 2018)
In Germany, around 200 billion euros are invested every year in knowledge-based capital, which encompasses assets such as research and development, software and databases, organizational capital, marketing and advertising, and technical design. Yet investments in traditional capital (such as machinery and non-residential buildings) still significantly outweigh knowledge investments, standing at over 320 billion euros across the whole economy. Nevertheless, at the sector level, manufacturing, information and communication services, professional services, and financial services stand out: Investments there are dominated by knowledge-based capital. More importantly, in the years since the financial crisis, there has been no increase in the investment intensity in knowledge-based assets. DIW Berlin compiled a novel dataset on company investments in knowledge-based capital covering almost 2 million records to explore the relationship between investments and company productivity. Initial results show that knowledge-based capital has a positive effect on productivity of comparable magnitude for all the different assets measured. Furthermore, intangible assets complement material assets-therefore, investments in traditional capital goods should always be accompanied by investments in intangible assets. An economic policy to increase investment needs to take these interdependencies into account and emphasize the importance of strengthening intangible assets.
Keywords: E22; D24; C23; 330; KBC; intangibles; TFP; productivity